2016
DOI: 10.18849/ve.v1i3.41
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mobile Devices and Online Services by German Veterinary Students

Abstract: Objective: The research question of our study was to determine the adoption and use of mobile devices and online services by veterinary students.Background: New technologies support learning, communication and information transfer during the preprofessional years and the professional lifetime. Hence, mobile devices may also be a feasible tool for information access for the practitioner at any place and any time, and consequently may support better informed clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Among ICT tools, mobile based applications are gaining a huge popularity now-a-days, because of their easy access and faster dissemination of information. Kasch et al, (2016) in a study reported that veterinary students and the next generation of veterinary practitioners are using mobile devices to a great extent and suggested that new information tools through mobile devices may help veterinarians to seek and share information. To promote commercial pig farming and also to enrich the veterinarians, a mobile app 'pig master' was developed based on the information needs of field veterinarians of Andhra Pradesh and the effectiveness of mobile app was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Among ICT tools, mobile based applications are gaining a huge popularity now-a-days, because of their easy access and faster dissemination of information. Kasch et al, (2016) in a study reported that veterinary students and the next generation of veterinary practitioners are using mobile devices to a great extent and suggested that new information tools through mobile devices may help veterinarians to seek and share information. To promote commercial pig farming and also to enrich the veterinarians, a mobile app 'pig master' was developed based on the information needs of field veterinarians of Andhra Pradesh and the effectiveness of mobile app was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporarily, the introduction of cutting-edge technologies, including smartphones, laptops, tablets, computers, wearable devices, and faster internet access, has also revolutionized the field of veterinary science and veterinary education [15,16]. This has resulted in an expansion of electronic device usage in educational settings altogether, with an augmentation of online resources accessed by veterinary students [3,17,18]. The global spread of COVID-19 has accelerated the integration of digital devices and online resources in veterinary medical education [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%